Segmental duplications and gene conversion: Human luteinizing hormone/chorionic gonadotropin β gene cluster - Hallast, Pille (Cold Spring Harbor Laboratory Press, 2005)
Segmental duplicons (>1 kb) of high sequence similarity (>90%) covering >5% of the human genome are characterized by complex sequence variation. Apart from a few well-characterized regions (MHC, β-globin), the diversity and linkage disequilibrium (LD) patterns of duplicons and the role of gene conversion in shaping them have been poorly studied. To shed light on these issues, we have re-sequenced the human Luteinizing Hormone/Chorionic Gonadotropin β (LHB/CGB) cluster (19q13.32) of three population samples (Estonians, Mandenka, and Han). The LHB/CGB cluster consists of seven duplicated genes critical in human reproduction. In the LHB/CGB region, high sequence diversity, concentration of gene-conversion acceptor sites, and strong LD colocalize with peripheral genes, whereas central loci are characterized by lower variation, gene-conversion donor activity, and breakdown of LD between close markers. The data highlight an important role of gene conversion in spreading polymorphisms among duplicon copies and generating LD around them. The directionality of gene-conversion events seems to be determined by the localization of a predicted recombination “hotspot” and “warm spot” in the vicinity of the most active acceptor genes at the periphery of the cluster. The data suggest that enriched crossover activity in direct and inverted segmental repeats is in accordance with the formation of palindromic secondary structures promoting double-strand breaks rather than fixed DNA sequence motifs. Also, this first detailed coverage of sequence diversity and structure of the LHB/CGB gene cluster will pave the way for studying the identified polymorphisms as well as potential genomic rearrangements in association with an individual's reproductive success.